A qualitative study of smoking within a Western Sydney Arabic‐speaking community: a focus on men in the context of their families. (24th March 2015) - Phillips, Anastasia; Monaem, Abdul; Newman, Christine
Abstract : Issue addressed: Smoking rates are high among Arabic‐speaking populations, particularly men, and there is limited evidence to formulate effective tobacco‐control strategies in this group. This study explored smoking within an Arabic‐speaking community in Sydney, focusing on men's smoking in the context of their families. Methods: We conducted six focus groups with a total of 60 Arabic‐speaking participants recruited through health workers, counsellors and community leaders in Western Sydney, Australia. The focus groups, conducted in Arabic or English, discussed smoking experiences, family issues and quit attempts. Focus group data were recorded, transcribed and analysed for emerging themes. Results: Male smoking was normalised in home, social and religious settings. There was concern about children's exposure to environmental tobacco smoke (ETS), but less concern for adults, particularly wives. Smoking created conflict within families and quit attempts were often made without assistance. There was a lack of enthusiasm for telephone support services with participants suggesting free Nicotine Replacement Therapy (NRT) and programs in religious settings as potential strategies. Conclusions: Smoking is normalised in Arabic‐speaking society and is socially acceptable. Strategies to de‐normalise smoking, particularly among men, are critical. Ongoing ETS exposure of wives is concerning and suggests the need to empower women to control their exposure. There is an opportunity to create locally tailored interventions by engaging leaders in religious settings and to improve perceptions of telephone support services. So what?: Culturally appropriate strategies to de‐normalise smoking for Arabic‐speaking male smokers are needed together with novel approaches that incorporate families and involve community leaders.